The Need for Ethics Audit: Its Relevance and Importance in Government Organizations (Case Study of Indonesian Government) - Setiawaty, Agus; Ludigdo, Unti; Adib, Noval (The International Journal of Accounting and Business Society, 2023)
Purpose—This paper aims to explore the emergent discourse of ethics audit and advance the relevance and importance of ethics audit as an effective way of maintaining an ethical climate in Indonesian government organizations.  Design/Methodology/Approach—This study uses a qualitative approach with Constructivism-Grounded Theory (CGT) analysis to gather field data and find, explore, and formulate findings. CGT is used because the conceptual foundation regarding ethics audit is still developing.  Findings—The findings obtained are that the ethics audit proposed in this study is significantly relevant to creating a better ethical climate in government organizations in Indonesia. The relevance involves an analysis of 3 perspectives, namely the micro, meso, and macro levels. The ethics audit model is proposed to provide a design for action in mitigating ethics violations, a framework to achieve good government governance, and a strategy for governing integrated continuous auditing. Practical Implication—In a situation where the issue of public officials' ethics is being seriously highlighted in society, this study promotes the importance of ethics audits to government organizations. It is hoped that ethics audits will be legitimized as annual practices like the predecessor audits that already exist.  Originality/Value—This study fills the void of the limited discourse on ethics audits in Indonesia. Findings from this research raise the government’s awareness to be more serious about ethics through ethics audits.